Benthic foraminifers and thecamoebians from Guaratuba Bay (Paraná, Brazil): Spatial distribution and trophic interactions with carbon sources - Disaró, Sibelle Trevisan; Roda, Fernanda Neves Daichtman; Kolm, Hedda Elisabeth (Anuário do Instituto de Geociências, 2006)
Abstract